Effect of soluble sulfur species on the electrochemical behavior of lithium–sulfur batteries with dual-phase electrolytes. Issue 8 (24th June 2019) - Zhao, Chengcheng; Yang, Hao; Wang, Xiaofei; Li, Huilan; Qi, Chu; Wang, Lina; Liu, Tianxi
Abstract : We report a Li–S system with dual-phase electrolytes by taking advantage of the highly soluble lithium polysulfides (Li2 S n, 2 < n ≤ 8), and it shows an improved reaction kinetics associated with a low interfacial charge transfer resistance. Abstract : Lithium polysulfides (Li2 S n, 2 < n ≤ 8) are investigated as a catholyte for lithium–sulfur (Li–S) batteries with dual-phase electrolytes. The combined electrochemical and morphological investigation reveals that the cell with Li2 S n shows higher electrochemical activity and faster reaction kinetics compared to that with S8, providing an attractive alternative for high energy density rechargeable flow batteries.